Synthesis and Biological Evaluation of Novel Cationic Rhenium and Technetium-99m Complexes Bearing Quinazoline Derivative for Epidermal Growth Factor Receptor Targeting - Sotiria Triantopoulou; Ioanna Roupa; Antonio Shegani; Nektarios N. Pirmettis; Georgia I. Terzoudi; Aristeidis Chiotellis; Maria Tolia; John Damilakis; Ioannis Pirmettis; Maria Paravatou-Petsota (MDPI AG, 2024)
Background/Objectives: Epidermal growth factor receptor (EGFR) plays a vital role in cell proliferation and survival, with its overexpression linked to various malignancies, including non-small cell lung cancer (NSCLC). Although EGFR tyrosine kinase inhibitors (TKIs) are a key therapeutic strategy, acquired resistance and relapse remain challenges. This study aimed to synthesize and evaluate novel rhenium-based complexes incorporating EGFR TKIs to enhance anticancer efficacy, particularly in radiosensitization. Methods: We synthesized a rhenium tricarbonyl complex (Complex 2) and its 99mTc analog (Complex 2') by incorporating triphenylphosphine instead of bromine as the monodentate ligand and <semantics><msubsup>PF6−</msubsup></semantics> as the counter-ion, resulting in a positively charged compound that forms cationic structures. Cytotoxicity and EGFR inhibition were evaluated in A431 cells overexpressing EGFR using MTT assays, Western blotting, and flow cytometry. Radiosensitization was tested through MTT and clonogenic assays. The 99mTc complex's radiochemical yield, stability, and lipophilicity were also assessed. Results: Complex 2 exhibited significant cytotoxicity with an IC50 of 2.6 μM and EGFR phosphorylation inhibition with an IC50 of 130.6 nM. Both complex 1 and 2 induced G0/G1 cell cycle arrest, with Complex 2 causing apoptosis. Radiosensitization was observed at doses above 2 Gy. Complex 2' demonstrated high stability and favorable lipophilicity (LogD7.4 3.2), showing 12% cellular uptake after 30 min. Conclusions: Complexes 2 and 2' show promise as dual-function anticancer agents, offering EGFR inhibition, apoptosis induction, and radiosensitization. Their potential as radiopharmaceuticals warrants further in-depth investigation in preclinical models.